Ease and Difficulty in L2 Pronunciation Teaching: A Mini-Review - O’Brien, Mary Grantham (Frontiers in Communication, 2021)
Both L2 learners and their teachers are concerned about pronunciation. While an unspoken classroom goal is often native-accented speech (i.e., a spoken variety of the mother tongue that it not geographically confined to a place within a particular country), pronunciation researchers tend to agree that comprehensible speech (i.e., speech that can be easily understood by an interlocutor) is a more realistic goal. A host of studies have demonstrated that certain types of training can result in more comprehensible L2 speech. This contribution considers research on training the perception and production of both segmental (i.e., speech sounds) and suprasegmental features (i.e., stress, rhythm, tone, intonation). Before we can determine whether a given pronunciation feature is easy or difficult to teach and—more importantly—to learn, we must focus on: 1) setting classroom priorities that place comprehensibility of L2 speech at the forefront; and 2) relying upon insights gained through research into L2 pronunciation training. The goal of the mini-review is to help contextualize the papers presented in this collection.